Barriers and Facilitators to Adherence to a Healthy Diet Across the Spectrum of Chronic Kidney Disease - Trigueros-Flores XB; Luna-Hernández G; Santos-Lopez MF; Pérez-Galván L; Flores-Camacho KJ; Díaz-Canchola LM; Cueto-Manzano AM; Chávez-Chávez HE; Cerrillos-Gutiérrez JI; Rojas-Campos E; Martín-del-Campo F (Patient Preference and Adherence)
Xochitl B Trigueros-Flores,1 Gabriela Luna-Hernández,2 María F Santos-Lopez,1 Lucía Pérez-Galván,1 Karen J Flores-Camacho,1 Laura M Díaz-Canchola,3 Alfonso M Cueto-Manzano,1 Hugo E Chávez-Chávez,3 Jose I Cerrillos-Gutiérrez,4 Enrique Rojas-Campos,1 Fabiola Martín-del-Campo1 1Unidad de Investigación Médica en Enfermedades Renales, Hospital de Especialidades CMNO, IMSS, Guadalajara, Jalisco, México; 2Centro Universitario de Ciencias de la Salud, Universidad de Guadalajara, Guadalajara, Jalisco, México; 3División de Medicina Interna, Hospital General Regional 180, IMSS, Guadalajara, Jalisco, México; 4División de Nefrología y Trasplantes, Hospital de Especialidades CMNO, IMSS, Guadalajara, Jalisco, MéxicoCorrespondence: Fabiola Martín-del-Campo, Unidad de Investigación Médica en Enfermedades Renales, Hospital de Especialidades, CMNO, IMSS, Belisario Domínguez No. 1000, Col. Independencia, Guadalajara, Jalisco, CP 44320, México, Tel +52 (33)1071-1190, Email fabi_mc@hotmail.comPurpose: A healthy diet plays an important role for chronic kidney disease (CKD) treatment, but adherence to nutritional recommendations is frequently low. The aim of the present study was to describe barriers and facilitators to adherence to a healthy diet in people with CKD.Patients and Methods: Cross-sectional study; 80 predialysis (n=20), hemodialysis (n=20), peritoneal dialysis (n=20) and transplant (n=20) patients matched by age and sex, were included. Nutritional evaluation included subjective global assessment, anthropometry, quality of food consumption (Mini-ECCA v.2), self-perception about diet and willingness to change. Barriers and facilitators were evaluated with a qualitative approach (semi-structured interviews). Concepts were converted into “in vivo” and “theoretical” codes, then, grouped into categories. A second analysis was performed with the ATLAS.ti software.Results: Frequency of malnutrition was 50% in people receiving dialysis. Quality of food consumption was healthier on people with CKD stages 3b-5 (40%) and people with kidney transplant (65%) compared to peritoneal dialysis (25%) and hemodialysis (0%). The main themes influencing adherence to a healthy diet were: need for nutritional guidance, economy, dietary restrictions, willingness to change, relationship with consequences in disease control and health status, aversion for healthy foods, bad and good self-perception, family support, feelings and emotions, environment, eating habits and CKD itself. Lack of time, work, economy, food preferences and cravings were the main barriers in people with CKD stage 3b-5 and transplant, while low willingness to eat healthy foods and dietary restrictions were the main barriers in people receiving dialysis.Conclusion: Personal, environmental, health professional-related, CKD related as well as feelings and emotions aspects that people with CKD face in a daily basis, act as barriers or facilitators when trying to follow a healthy diet. Individualizing nutritional treatment taking into account people with CKD perspectives and situations is of utmost importance to improve adherence to nutritional treatment.Plain summary: In this article, the authors discuss the main barriers and facilitators that people with kidney disease face when trying to follow a healthy diet (from the people with CKD perspective). A healthy diet has been associated with lower progression of kidney disease and helps to prevent complications; however, adherence to nutritional recommendations is frequently low. People on dialysis had the unhealthier diet compared to people on predialysis or kidney transplant. People perceived dietary restrictions, lack of nutritional counseling and knowledge, economic constraints, lack of social and family support, negative effects of food on their health, dislike or aversion to healthy foods, lack of time and environment limitations as the main barriers to adhere to a healthy diet.Additionally, since diets are considered complicated (especially renal diets), strategies to improve willingness to eat healthy, counseling about food variety and preparation, some liberalization of dietary restrictions (when possible) and considering family support could help people with CKD to increase skills to adhere to a healthier diet. Considering people with CKD perspectives is of utmost importance when planning nutritional treatment and counseling, to improve adherence and therefore, clinical outcomes.Keywords: healthy diet, treatment adherence, qualitative research, chronic renal insufficiency